Βιβλιοκρισία: David ROLLASON, The Power of Place, Rulers and their Palaces, landscapes, cities, and holy places, Princeton – Oxford: Princeton University Press 2016 - VEIKOU, Myrto (Byzantina Symmeikta, 2018)
Βιβλιοκρισία: David ROLLASON, The Power of Place, Rulers and their Palaces, landscapes, cities, and holy places, Princeton – Oxford: Princeton University Press 2016